The prevalence of sarcocystis species in sheep - Ferda Sevinç; Funda Altınöz; Uğur Uslu; Osman Selçuk Aldemir (Eurasian Journal of Veterinary Sciences)
A total of 511 sheep brought to Konet Abattoir in Konya were examined for infections with Sarcocystis spp. using macroscopic and microscopic methods for detection from January to April 2000. Macroscopic cysts ranging from 2 to 257 cysts per oesophageal muscle were found in 19,76 % of the sheep. Microscopic cysts were found in 92.95 % of the sheep with the use ol tripsin method. Three types of microscopic cysts were detected with differences in their cyst walls morphologicalty. These microscopic cyst species were S.ovicanis. s ovıielis. S.arieticanis.